Doing it when others do: A strategic model of procrastination - Claudia Cerrone (Max Planck Institute for Research on Collective Goods, 2016)
This paper develops a strategic model of procrastination in which present-biased agents prefer to do an onerous task in the company of someone else. This turns their decision of when to do the task into a procrastination game a dynamic coordination game between present-biased players. The model characterises the conditions under which interaction mitigates or exacerbates procrastination. Surprisingly, a procrastinator matched with a worse procrastinator may do her task earlier than she otherwise would: she wants to avoid the increased temptation that her peer's company would generate. Procrastinators can thus use bad company as a commitment device to mitigate their self-control problem. Principals can reduce procrastination by matching procrastinators with each other, but the efficient matchingmay not be stable.
Keywords: C72; C73; D03; D91; 330